Avaliação da dor pós-operatória em tratamentos endodônticos de sessão única ou múltipla e seus aspectos moleculares: um estudo clínico. - Rosa, Larissa Nunes (2020)
The objectives of this study were to compare the incidence and intensity of postoperative pain after endodontic therapy in a single and multiple session, in cases of necropulpectomy, through a randomized controlled clinical study and to evaluate the relationship between the patient's state of anxiety, in view of the treatment and its perception of pain, in addition to the presence of genetic polymorphisms in the DRD2, ANKK1 and COMT genes and their relationship with pain after endodontic treatments. Sixty-seven patients were included in the first part of the research, 34 in the single session group and 33 in the multiple session group. In the second part, a sub-sample with 25 patients was selected. The endodontic treatment was performed by graduate students, with previous training in used technique. Before the procedure, saliva was collected for genetic evaluation and the State-Trait Anxiety Inventory (STAI-E) was applied to assess the patients' state of anxiety at the time of endodontic treatment, in the 25 patients subsample. The presence of postoperative pain was assessed as “yes” or “no”, and the intensity by Visual Analogue Scale (VAS), three times after treatment (24, 48 and 72 hours). The data obtained were submitted to statistical analysis, using Student's t-test, Mann-Whitney test, Fisher's exact test, Friedman's non-parametric test and Wald's test and were fitted in a logistic regression model. The data referring to postoperative pain were analyzed and the number of sessions showed no significant difference for the presence of postoperative pain (p = 0.806). Teeth without periapical lesion had a higher frequency of postoperative pain (p = 0.048) and the pain was more intense in the first 24 hours in both the single session group (p <0.001) and in the multiple session group (p <0.001) compared to the other times evaluated. In the sub-sample there was an association between moderate anxiety (STAI-E) and postoperative pain in both groups, a single session (p = 0.028) and multiple sessions (p = 0.032). There were no significant differences between individuals with and without pain when the ANKK1 gene (p = 0.60), the DRD2 gene (p = 0.81) and the rs165656 polymorphism in the COMT gene (p = 0.33) were evaluated. In the rs174675 polymorphism of the COMT gene, there was an association with postoperative pain (p = 0.018), individuals with CT alleles had more postoperative pain when compared to those with CC alleles. It can be concluded, with the results obtained, that the number of sessions was not associated with a higher incidence of postoperative pain, patients who were classified as having moderate anxiety had an association with a higher incidence of postoperative pain as well as patients that showed rs 174675 polymorphism of the COMT gene when comparing the CT and CC alleles.